1975
DOI: 10.3758/bf03213439
|View full text |Cite
|
Sign up to set email alerts
|

The rat’s long-term preference for complexity in its environment

Abstract: Locomotor, resting, and feeding responses to four levels of environmental complexity were measured in a two-phase study. In a long-term free-choice testing situation (ad-lib phase), subjects (N'" 20) demonstrated a marked preference for high complexity during "day" conditions. This preference, present in the patterns of resting and locomotor behavior, was partially preserved under "night" conditions. The patterns of feeding behavior were essentially independent of complexity preference. The same subjects in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
2

Year Published

1979
1979
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 15 publications
2
7
2
Order By: Relevance
“…The finding that rats in the novelty condition spent more time eating than those in the complexity condition has parallels with findings that unenriched rats spend more time feeding than those in enriched cages (Denny, 1975;Fiala et al, 1977;Townsend, 1997;Zaias et al, 2008). The more limited set of alternative activities available in the novelty condition may have promoted increased eating behaviour, as may have the larger amount of time spent under the food hopper (which was positively correlated with the total time spent feeding).…”
Section: Discussionsupporting
confidence: 64%
“…The finding that rats in the novelty condition spent more time eating than those in the complexity condition has parallels with findings that unenriched rats spend more time feeding than those in enriched cages (Denny, 1975;Fiala et al, 1977;Townsend, 1997;Zaias et al, 2008). The more limited set of alternative activities available in the novelty condition may have promoted increased eating behaviour, as may have the larger amount of time spent under the food hopper (which was positively correlated with the total time spent feeding).…”
Section: Discussionsupporting
confidence: 64%
“…However, even in the case of SC rats, which were reared in standard laboratory conditions, our results actually are not in agreement with those found in literature: in most studies, the rats showed a strong preference for complexity (e.g. Baker & Franken, 1967;Dember, Earl, & Paradise, 1957;Denny, 1975) or, at least, a preference for a moderate or optimal level of complexity (e.g. Berlyne, 1960;Dutch & Brown, 1971, May, 11968).…”
Section: Discussioncontrasting
confidence: 56%
“…We should stress that this observation is in conflict with Denny's (1975) observations on isolated rats: Denny noticed, first, that a preference for complexity exists and, second, that this preference was stronger during the daytime. These results were interpreted by him as a shelter/relaxation seeking response elicited by the number or complexity of elements in the complexity area.…”
Section: Discussioncontrasting
confidence: 47%
“…This may help explain why, on average, the rats (n ¼ 20) spent four times longer in a 'high' complexity environment (highest density and diversity of chains hanging from cage roof) than in a medium or low complexity environment, engaging in significantly higher rates of ambulation and resting activity (Denny 1975). Male Wistar rats kept in a standard cage with (n ¼ 10) and without (n ¼ 10) a propylene cage insert strongly preferred the altered cage to the empty one in two-way choice tests lasting 8 h for each subject (Townsend 1997).…”
Section: B Environmental Complexitymentioning
confidence: 99%